Rancang bangun mesin press baglog untuk pembuatan media tanam bibit jamur merang - Deri Teguh Santoso; Ratna Dewi Anjani; Rianita Puspa Sari; Febri Aljabar (Department of Mechanical Engineering, University of Udayana, 2021)
Mushroom baglog machine is used to assist mushroom farmers in producing mushroom seedling media. It works by compressing baglog media to make it tightly packed and slicing straw for planting media. Because mushroom seeds are bundled in bags (bags) in the shape of compressed logs, the mushroom growth media is sometimes called baglog. Compaction of mushroom seedling medium seeks to enhance the density of the media and its capacity to absorb water. The approach of building a mushroom baglog press machine with low power consumption is appropriate for small farmers' demands. To build a mushroom baglog press machine, numerous machine parts must be designed according to the requirements of the electric motor, belt, pulley, chain, sprocket, and shaft, as well as the convenience of operation. The calculations assume a power output of 0.5 hp, a rotational speed of 1420 rpm, and a transmission ratio of 1:60. The shear stress value on the step shaft in the punch is an accurate measurement, indicating that the design stress is greater than the actual stress.